Job satisfaction of medical librarians in Quezon City and Metro Manila - Estillore, Regine Cecilia P. (2009)
Medical libraries cater to the information needs not only of doctors but also students, allied health sciences professionals, and even non-medical professionals. One of the key factors to providing quality service to clients is job satisfaction. Medical librarians that are satisfied with their jobs are able to be more efficient and effective in their jobs. In relation to this, this study aimed to determine the job satisfaction of librarians from selected medical and allied health sciences libraries in Quezon City and Metro Manila. Their satisfaction was based on the elements in Maslow's hierarchy of needs. Age, gender, educational attainment, length of service, salary, and type of hospital were also studied to determine if there is a correlation between the given variables and their job satisfaction.